Investigating communicative barriers on construction industry productivity in Malaysia: An overview - Khairul Firdaus Ne'Matullah; Lim Seong Pek; Siti Aisyah Roslan (International Journal of Evaluation and Research in Education (IJERE), 2021)
The evolution of technology has changed the way how human communicate in the current time. With the advancement of technology, instructions and messages could be delivered in a split second. Even though life is made easy with technology, some information and details should be delivered face-to-face in order to avoid communication breakdown. This study was carried out to determine the language needs by foreign workers working at construction sectors in Malaysia. The study created an overview on how communication affects productivity in completing tasks on time. The results from this study lead to a development of language modules for foreign workers training. An online survey was carried out through social media on construction site supervisors around Malaysia in getting their feedback related to the origin of their co-workers and the importance of English language as medium of instruction for task fulfilment. Results indicated that language barriers had affected productivity in the sector of construction in Malaysia. Besides, results also noted that cross-cultural differences had put foreign workers at risk and caused wastage to time and manpower.